Assessment of Physicochemical and Microbiological Quality of Drinking Water from Chembarambakkam Lake, Tamil Nadu, India - Rajkumar, B.; Yogesh, M.; Akila, N.; Yogananth, N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Backgrounds: A wide variety of life forms can be found in inland surface waters, especially lakes, which are also very productive ecosystems. The primary source of lake water contamination stems from poor sanitation practices, including the inflow of drainage systems and excess runoff into these water bodies. Hence, a comprehensive understanding of the microbial and physicochemical qualities of drinking water is essential for human health. Aim of the Works: The aim of this study was to assess the water quality of Chembarambakkam Lake by comparing its microbiological and physicochemical parameters with established drinking water standards, as well as examining the impact of various domestic and industrial effluents. Methodology: The physicochemical parameters including pH, turbidity, electrical conductivity (EC), total dissolved solids (TDS), Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), dissolved oxygen (DO),calcium (Ca2+), magnesium (Mg2+),fluoride (F −), chloride (Cl– ),nitrate (NO3), sulphate (SO4 2–) were analysed. Microbial content (coliforms) determined by Most Probable Number (MPN) method. Results: The water sample collected were colourless and odourless and the turbidity of the lake water was 1.2 NTU, which is well below the recommended standard for drinking water (5.0 NTU). The electrical conductivity measured was 1243 µS/cm, which is also within the permissible limit of 2500 µS/cm for drinking water. The chemical analysis revealed that the lake water contains dissolved minerals such as calcium (36 mg/L) and magnesium (10.7 mg/L). The microbiological analysis revealed the presence of coliforms, fecal coliforms, and E. coli at levels lower than the maximum colony count permitted by the Food Act. Conclusions: The present study showed a significant association between the water quality parameters and the microbial content, indicating that the water from the lake is suitable for drinking. However, continuous monitoring of water quality is recommended to prevent the spread of waterborne diseases that pose significant health risks.